Readiness Society to Enter the Era of Halal Drug Certification Mandatory in Terms of Knowledge, Perceptions, and Attitudes - Ahmad Azrul Zuniarto; Nurkhasanah Mahfudh; Dyah Aryani Perwitasari; Siti Pandanwangi (Postgraduate, University of Mataram, 2024)
The halal lifestyle trend is currently developing in various regions of the world, not only in areas where the majority of the population is Muslim but also where the population is Muslim minority. This study aims to determine the level and correlation of public knowledge, perceptions, and attitudes toward halal medicine and correlation with demographic data. This cross-sectional study was conducted online using a validated questionnaire, conducted in January-February 2023 on 600 respondents in six provinces of Java Island, using a purposive sampling method with inclusion criteria over 17 years old and exclusion criteria not being a doctor or pharmacist. The Spearman test was used to correlate knowledge-perception-attitude, and the Chi-square test was used to correlate demographic data with knowledge, attitude, and perception. The results showed that the level of public knowledge was sufficient (mean score 33.74 ± 2.37), the perception was sufficient (mean score 35.91 ± 3.47) and the attitude was sufficient (mean score 31.17 ± 4.25) towards halal medicine. Age, education, and place of work affect knowledge; and place of work affects perception. It is concluded that the community has sufficient knowledge, perceptions, and attitudes, knowledge-perception is significantly correlated, knowledge-attitude is weak and perception-attitude is strongly correlated